Urgensi Kompotensi Pemimpin Dalam Mengelola Konflik Organisasi: Suatu Analisis dari perspektif Komunikasi Konflik - R. Firdaus Wahyudi; Suriati Suriati (LP2M IAI Muhammadiyah Sinjai, 2023)
Abstract The conflict is inevitable thing in an organization. The way in managing organization conflict determined the output feature of conflict. Poorly managed conflict affected to destructive effect or decreased organization’s performances. However, well or constructively conflict managing affected to advantages and able to enhance such organization performances. The important party in managing organization conflict is a leader, because a leader is a supreme authority in an organization. The quality of leader can be seen in his/her ability in managing conflict. This research was qualitative research through the use library research due to the leader’s competency in managing conflict or conflict management. In this research described that the leader competencies in managing conflict could be seen in: the leader ability in detecting early the organization conflict symptoms or signs, the leader anility in responding a conflict, the leader ability in implementing the use of strategies or methods in managing conflict (management conflict strategy, and a leader ability in creating the atmospheres and culture of organization’s competency in conflict.